Modelos de referencia para la restauración de paisajes altoandinos en la Sierra centro de Ecuador: conceptualización y criterios e indicadores de selección - Sánchez Contento, Mayra Alexandra (2024)
High Andean landscapes are socio-ecosystems located between the frontier of closed forest and perpetual snow. They are characterized by the presence of both natural and anthropogenic ecosystems that reflect the dynamics of production and conservation that occurs in the central Sierra of Ecuador. These high Andean landscapes are subjected to significant pressures that lead to the degradation of ecosystem services. The restoration of high Andean landscapes arises as a tool for recovering deteriorated areas while constructing resilient and sustainable multifunctional landscapes. Restoration in these environments carries several challenges, one of them is the definition of reference models that allow for the assessment of whether restoration objectives are being achieved. Currently, there is limited information on how to adequately conceptualize and identify reference models for restoration. This study specifically presents a proposal that guides the selection of reference models in high Andean landscapes of the central Sierra of Ecuador. To achieve this goal, a systematic literature review was conducted to identify key elements in the identification of reference models for six natural ecosystems and two anthropogenic ones. Among the identified criteria, aspects related to the structure, composition, and function of the ecosystems are addressed. In addition, social, edaphic, climatic, and landscape aspects are included, such as fragmentation and agricultural practices, among others. Based on these criteria, practical indicators were developed to guide the selection of reference models for project implementers in restoration efforts.